Implementation and Challenges of Resettlement Program in a Component City in Northern Negros Occidental, Philippines - Javier, Krizzia Joy; Palic, Anabelle (Technium Social Sciences Journal, 2025)
Worldwide, people are displaced for various reasons contributing to their struggle to get out of poverty; in the ASEAN, government committed to implementation of sustainable housing but challenges remain while the Philippines enacted laws to support the sustainability of housing programs but still there is high rate of displacement particularly in cities due to migration. Although local government units in the province are implementing housing programs, yet challenges in implementation turns out a priority. This study investigates the implementation of a housing resettlement program among implementers and beneficiaries. It aims to provide baseline data and address the critical research gap in the local resettlement programs in local government units. The component city, which is the locale of this study, was granted by the national government of 1,992 units for the families affected by the typhoon. As of July 2022, 1067 families were awarded the units, or only 53.6 percent. In this context, this study was conducted to determine the extent of implementation of the beneficiaries of the resettlement program when they are grouped according to type of ownership and number of households. Based on the results and findings, an action plan to enhance the implementation of the resettlement program was designed. This is a descriptive-comparative study using a survey questionnaire to gather primary data to measure the extent of implementation of the housing programs of the city in terms of sustainability indicators and the challenges encountered by the beneficiaries over 350 respondents. A comparative research design examines the differences and similarities within and across cases with different contexts using the designation of the respondents and the number of households. The overall extent of implementation was rated very great in practically all variables with implementers rating very great while beneficiaries as great; there were no significant differences in terms of number of households nor the type of ownership although challenges were encountered in the implementation. Findings suggests the need for enhancement of implementation which are contained in the action plan.